2018
DOI: 10.17721/1728-2713.82.08
|View full text |Cite
|
Sign up to set email alerts
|

Management of Lean Mining and Use of Mineral Resources of Ukraine

Abstract: The article proposes a patent protected proprietary technique for managing lean mining and use of mineral resources of Ukraine on the example of non-metallic minerals for construction. Proposed solution of the problem on the basis of the technological relationship between the production processes and the lean use of production products with forecasting the development of the extractive industry is new. Ukraine has significant reserves of rocks suitable for mining of building stone, construction sands and expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The number of risk factors depends heavily upon enterprise's management team competence, its ability to form adequately strategic goals and manage their achievement as well as upon skills to develop and implement innovative projects, manage both human and financial resources, and capabilities to run effective operational management of productive processes (Volkov & Horoshkova, 2018;Domínguez, Martínez, Piñón Peña, & Rodríguez Ochoa, 2019). Risk level can also be decreased significantly through skillful and economical use of material resources, equipment, and capital stock of the enterprise (Domingues, Baptista, & Diogo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The number of risk factors depends heavily upon enterprise's management team competence, its ability to form adequately strategic goals and manage their achievement as well as upon skills to develop and implement innovative projects, manage both human and financial resources, and capabilities to run effective operational management of productive processes (Volkov & Horoshkova, 2018;Domínguez, Martínez, Piñón Peña, & Rodríguez Ochoa, 2019). Risk level can also be decreased significantly through skillful and economical use of material resources, equipment, and capital stock of the enterprise (Domingues, Baptista, & Diogo, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Han 31 studied the influence of factors such as personal characteristics and the social environment of mine employees on the effect of enterprise safety commitment, which provided a new perspective for improving the efficiency of enterprise safety management. Studies have shown that good safety management 32,33 and targeted investment in manpower and material resources 34 can effectively reduce corporate safety risks. Among the many influencing factors, some factors are difficult to effectively control due to the external environment, and have a greater impact on enterprise safety risks than other factors.…”
mentioning
confidence: 99%